OP02 Comparison of sex-specific historical cardiometabolic trajectories in T2D patients by dementia status in England. (26th August 2022) - Lai, Heidi; Sharma, Angelica; Chang, Kiara; Sharabiani, Mansour; Bottle, Alex; Valabhji, Jonathan; Middleton, Lefkos; Majeed, Azeem; Millett, Christopher; Vamos, Eszter
Abstract : Background: People with type 2 diabetes (T2D) have a two-fold higher risk of dementia compared with the general population. However, mechanisms underlying this association remain unclear, and preventative strategies targeting diabetes-specific factors have not proven to be effective. Cardiometabolic factors present as potentially modifiable risks, but it is unclear if historical cardiometabolic trends among those diagnosed with dementia vs. those without dementia differ by sex. Methods: People with T2D aged >42 years from the Clinical Practice Research Datalink between 1999 and 2018 in England were matched without replacement by age (±5 years) and sex, using a 1:4 case-to-control ratio. Eight routinely measured cardiometabolic factors were investigated. Individuals' retrospective cardiometabolic trajectories, as presented by annual mean levels, were assessed for up to 20 years preceding the date of dementia diagnosis (dementia group) or last contact with healthcare (non-dementia group). Multivariable-adjusted multilevel piecewise and non-piecewise growth curve models were used to model cardiometabolic trajectories and stratified by sex. Results: Among 117, 730 people, 23, 546 developed dementia during follow-up (median 11 years). Females with dementia (n=13, 389) had higher systolic blood pressure (SBP) between 11–17 years prior to dementia diagnosis vs. non-dementia group, which was not observed in males; while males with dementia (n=10, 157) had significantly lower SBP from 9 years prior to diagnosis, as opposed to 7 years onwards for females. Mean SBP levels at diagnosis were 2.15 (1.94–2.35) mmHg and 1.47 (1.25–1.70) mmHg lower vs. non-dementia group for females and males, respectively. Lower levels of body mass index (BMI) in the dementia group were detected earlier among females (17 years preceding diagnosis) than males (12 years). At diagnosis, BMI was 1.51 (1.43–1.59) kg/m 2 and 0.72 (0.66–0.79) kg/m 2 lower vs. non-dementia groups for females and males, respectively. Higher levels of fasting plasma glucose were also observed earlier for females with dementia vs. non-dementia (from 12 years before diagnosis) than males (2 to 7 years prior to diagnosis). However, males with dementia had higher HbA1c levels from 8 years preceding diagnosis than females (6 years preceding diagnosis). While some differences were observed for diastolic blood pressure, cholesterol, high-density lipoprotein, and low-density lipoprotein between men and women, absolute differences between dementia and non-dementia groups were generally small. Conclusion: Among women in a T2D population, differences in cardiometabolic factors generally present earlier before dementia diagnosis compared with males, suggesting that future strategies could potentially be tailored for sex-specific subgroups when identifying potential targets for dementia prevention. (Funder: Diabetes UK No. 18/0005851)